2011
DOI: 10.1021/jm200566e
|View full text |Cite
|
Sign up to set email alerts
|

Selective Water-Soluble Gelatinase Inhibitor Prodrugs

Abstract: SB-3CT (1), a selective and potent thiirane-based gelatinase inhibitor, is effective in animal models of cancer metastasis and stroke; however, it is limited by poor aqueous solubility and extensive metabolism. We addressed these issues by blocking the primary site of metabolism and capitalizing on a prodrug strategy to achieve >5000-fold increased solubility. The amide prodrugs were quantitatively hydrolyzed in human blood to a potent gelatinase inhibitor, ND-322 (3). The arginyl amide prodrug (ND-478, 5d) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
62
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 41 publications
1
62
0
Order By: Relevance
“…However, since we were unsuccessful in demonstrating a significant reduction in cleaved MMP-9 activity 6 h after HI, we cannot discount the possibility that any remaining cleaved MMP-9 activity was at levels sufficient to counteract potential neuroprotective effects of SB-3CT. Given the lack of neuroprotection found with SB-3CT further investigations are warranted using recently developed selective water-soluble MMP gelatinase inhibitors that can be administered intravenously to evaluate the possibility of significant neuroprotection [38]. …”
Section: Discussionmentioning
confidence: 99%
“…However, since we were unsuccessful in demonstrating a significant reduction in cleaved MMP-9 activity 6 h after HI, we cannot discount the possibility that any remaining cleaved MMP-9 activity was at levels sufficient to counteract potential neuroprotective effects of SB-3CT. Given the lack of neuroprotection found with SB-3CT further investigations are warranted using recently developed selective water-soluble MMP gelatinase inhibitors that can be administered intravenously to evaluate the possibility of significant neuroprotection [38]. …”
Section: Discussionmentioning
confidence: 99%
“…Over the past several years we have produced a library of thiirane inhibitors for MMPs (10)(11)(12), which allowed the identification of specific inhibitors for selective inhibition of enzymes involved in various MMP-mediated diseases. The thiiranes undergo a reaction catalyzed by the target MMP, resulting in opening of the thiirane ring and generation of the thiolate, which is a tight-binding inhibitor (13).…”
Section: Significancementioning
confidence: 99%
“…Excisional wounds were made on the dorsal thorax of db/db mice, and the wounds were treated topically with vehicle, ND-336, or ND-322 (compound 2), which was used as a positive control. ND-322 inhibits MMP-9 as a slow-binding inhibitor with a K i of 870 ± 110 nM and inhibits MMP-8 as a linear noncompetitive inhibitor with a K i of 2,600 ± 400 nM, with a threefold selectivity for MMP-9 over MMP-8 (10). Wounds treated with ND-336 healed 1.2-to 1.6-fold faster than those treated with ND-322 and twofold faster than those treated with vehicle ( Fig.…”
Section: Significancementioning
confidence: 99%
“…Therefore, design of selective inhibitors against target MMPs that have tumor-promoting effects is needed. Pioneer studies aiming to develop selective MMP inhibitors recently have been reported (12)(13)(14)(15)(16)(17)(18).…”
mentioning
confidence: 99%